An emprical study toward students' academic performance and students' residential status / Faizan Abd Jabar … [et al.] - Abd Jabar, Faizan; Yahya, Wan Kalthom; Mohd Isnani, Zaidatulhusna; Abu, Zurah (2012)
Fundamentally, students are being judged through their academic performance. Excellence in education leads to good work ethic and a path of having a good job, good income as well as happy life in the future. Joining Universities is a challenge to students. Moreover, most of them may have to stay outside the campus due to shortage of hostel facilities. Unfortunately, based on people perception, students who live outside the campus usually will show a poor academic performance. Hence, this study was conducted as to prove the perception or otherwise. Besides that, this study analyzed the difference between students' academic performance and students' residential status. A structured questionnaire was distributed in the classroom to 245 students from part 5 and 6 from the Faculty of Business Management. SPSS version 20 was used to analyze the data. The outcome of the study would contribute insight information and recommendation to UiTM Jengka in particular and other higher-level institution on how to plan strategically in order to increase the students' academic performance.